2014
DOI: 10.1111/sdi.12310
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Cephalic Arch Stenosis With and Without Stent Placement after Percutaneous Balloon Angioplasty in Hemodialysis Patients

Abstract: Cephalic arch stenosis is a common complication in maintenance hemodialysis (MHD) patients with brachial artery-cephalic vein fistulas and frequently leads to loss of the functioning brachial artery-cephalic vein fistula. There is paucity of conclusive data to guide appropriate management. We examined the risk of recurrence of cephalic arch stenosis after angioplasty compared to angioplasty after stent placement determined by angiography of the involved upper extremity over time in a contemporary cohort of MHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 11 publications
0
27
1
2
Order By: Relevance
“…In the present prospective study, we observed 0% primary treatment area patency and 0% primary circuit access patency with PTA at 6 months. Although other studies (2,6) observed a 42% rate and a median 91-day access circuit patency period after PTA for CASs, these studies were retrospective (2,6). Even compared with these retrospective outcomes, we observed a 100% 6-month primary access circuit patency with stent-graft placement.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…In the present prospective study, we observed 0% primary treatment area patency and 0% primary circuit access patency with PTA at 6 months. Although other studies (2,6) observed a 42% rate and a median 91-day access circuit patency period after PTA for CASs, these studies were retrospective (2,6). Even compared with these retrospective outcomes, we observed a 100% 6-month primary access circuit patency with stent-graft placement.…”
Section: Discussioncontrasting
confidence: 67%
“…In another retrospective study of 45 CASs (6), median PTA patency interval was 91.5 days, with a suggestion of improved bare metal stent patency, with a median patency interval of 152 days. Although patency appeared improved with bare metal stents for CASs in this study (6), no description of intervention, follow-up methodology, points of censure, or definitions and estimation of patency were provided, making any comparison problematic. However, as observed by Shemesh et al (3), patency with stent grafts exceeds that observed with bare metal stents.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Elastic recoil was more common for stenoses within the cephalic arch compared with all other vein segments within the access circuit. This area was associated with lower technical success and patency after PTA compared with outcomes of PTA within other areas of the access circuit (12)(13)(14). Although the perpendicular portion of the vein is subject to shear forces, and external compression by the deltopectoral fascia was suggested for poorer outcomes, it is unclear if these factors also predispose to elastic recoil.…”
mentioning
confidence: 88%